English Affixation in Translated Short Stories: Student Error Analysis - Nurwegya Dehi; Bay, Indri Wirahmi; Ali, Sri Widyarti (Universitas Veteran Bangun Nusantara, 2023)
This research scrutinizes the prevalent issue of English affixation errors in the writing of EFL students. These errors have substantial implications for the semantic accuracy of translated words from the student's native language into English. The study focuses on errors in short stories translated by students from Translation Class at the English Education Study Program of Universitas Negeri Gorontalo. The research objectives encompass the identification and categorization of errors in English affixation usage and an exploration of their underlying causes. Dulay, Burt, and Krashen's error classification framework (2016), including omission, addition, misformation, and misordering, is employed and adapted for specific categories of English affixation errors. The study also investigates the causes of these errors, including interlingual transfer, intralingual transfer, context of learning, and communication strategies, as outlined by Brown (2014). Utilizing a qualitative descriptive research approach, the study provides a comprehensive analysis of error types and their causative factors related to affixation. Drawing upon Ellis's data analysis technique (1997), the researchers identify, describe, and explain these errors. The findings reveal omission as the most prevalent error, followed by misformation and addition, each encompassing inflectional and derivational affixes. Notably, the inflectional suffix -ed, signifying the past tense, is a recurrent source of errors. These errors predominantly stem from intralingual transfer, with contextual learning, interlingual transfer, and communication strategies also contributing. In summary, differences in affixation usage between Indonesian and English significantly impact student translations of short stories.